Dark Southern Drywood Termite (suggested common name) Kalotermes approximatus Snyder (Insecta: Blattodea: Kalotermitidae) - Joseph F. Velenovsky; Rudolf H. Scheffrahn (EDIS)
Dark southern drywood termites are classified as “an uncommon structural pest,” though some infestations have been recorded. Learn to identify this termite species and get information about its distribution, history, biology, and management in this 5-page fact sheet written by Joseph F. Velenovsky and Rudolf H. Scheffrahn and published by the UF/IFAS Department of Entomology and Nematology.